Human rights theory and practice - Goodhart, Michael E. 1969- (Oxford University Press, 2023)
Human Rights: Theory and Practice is a comprehensive, interdisciplinary text written by a global team of experts with coverage and content unrivaled by any other text on the market. With contributions from an international panel of experts, including political scientists, lawyers, philosophers, and policy-makers, this text is unmatched in its ability to provide students with a practical, comprehensive and 21st century perspectives on the theory, study and practice of human rights"--